Prevalence and clinical characteristics of rotavirus diarrhea in Mataram, Lombok, Indonesia - Wayan Sulaksmana Sandhi Parwata; Wayan Sukardi; Abdul Wahab; Yati Soenarto (Indonesian Pediatric Society, 2016)
diarrhea and dehydration among children aged <5 years in developed and developing countries, including Indonesia. There have been few studies on the prevalence of rotavirus diarrhea in Mataram.Objective To determine the prevalence and characteristics of rotavirus diarrhea in children under five years of age with acute diarrhea in Mataram.Methods A cross sectional study using the WHO Generic Protocol for Rotavirus Surveillance was conducted in the Nusa Tenggara Barat (NTB) General Hospital, Mataram, as part of a multicenter study by the Indonesian Rotavirus Surveillance Network (IRSN) for children under five years of age. Subjects were diagnosed with rotavirus diarrhea based on stool sample examinations, using RT-PCR for genotyping. They were admitted to the Pediatrics Ward of the NTB Provincial General Hospital from January to December 2010.Results Of 329 children admitted with acute diarrhea, 210 (63.8%) had rotavirus positive stool specimens. For the year 2010, the highest incidence of rotavirus infection was in the month of January (86.4%). Rotavirus infections were found in children less than 2 years of age (65.4%), with the highest prevalence in the age group of 6 to 23 months (68.5%). In addition to clinical symptoms of watery diarrhea, there was a significantly greater percentage of vomiting in rotaviral vs. non-rotaviral diarrhea (67.7% vs. 32.3%, respectively; P<0.05). The majority of G and P genotypes found were G1 (86%), G2 (12%), P[8] (66%), P[4] (12.8%), and P[6] (8%).Conclusion Rotavirus infections are the most common cause of acute diarrhea in children aged <2 years in Mataram, Indonesia.